Behaviour-based robotic assembly systems reliability of behavioural modules - Wilson, Myra S. (1993)
Abstract: "This paper examines a method of improving the reliability of a Behaviour-based robotic assembly system. Robotic assembly systems in general suffer from the problem of variation and uncertainty build up which causes failure to complete the assembly correctly. The Behaviour-based approach to robotic assembly looks at decomposing the task into modular units, called Behavioural Modules, which reliably perform the assembly task. Even so, these Behavioural Modules can still fail due to the workcell conditions being outwith their competence. This paper examines a method of using appropriate localised information to provide alternatives in the event of such a failure. This introduces the concept of Exit States (which inform the system of which internal control path was taken through a Behavioural Module), the Ideal Execution Path (the best control route through the hierarchy of Behavioural Modules), and Alternative Execution Paths (an alternative control route containing Behavioural Modules which can be used in the event of failure).
Keywords: Bionics and artificial intelligence; Robotics and its application; Robotics